Traumatic Cervical Spondyloptosis in a Neurologically Stable Patient: A Therapeutic Challenge - Sunil Munakomi; Binod Bhattarai; Iype Cherian (Case Reports in Critical Care, 2015)
This is a case report of a neurologically intact patient following posttraumatic cervical spondyloptosis. We discuss the disease, management protocol and some surgical nuances to prevent any damage to the cord during different stages of its treatment.